Improving operational plant performance in international manufacturing networks: the effects of integrative capabilities and plant roles. Issue 2 (17th February 2019) - Arellano, Maricela C.; Rebolledo, Claudia; Tao, Zhexiong
Abstract: This study adopts the resource-based view to examine how two integrative capabilities of a plant embedded in a manufacturing network enhance operational performance: the capability to connect with other plants in its manufacturing network (a networking capability, NC), and the capability to integrate manufacturing processes with new product development processes (a new product development capability, NPDC). Our model tests the indirect effect of NC on cost, quality, flexibility and delivery through NPDC. Furthermore, we test if the relationship between NC and NPDC depends on the strategic role of the plant. Using survey data from a sample of 521 plants, we confirmed the mediating effect of NPDC. However, the moderation effect was not confirmed. Our findings reveal that plants can deploy NPDC capabilities, fostered by NC, independently from their role in the network. This study contributes to the understanding of plant capabilities and plant roles in manufacturing networks.